1992
DOI: 10.1086/132983
|View full text |Cite
|
Sign up to set email alerts
|

Coronal X rays from single, magnetic white dwarfs - A search and probable detection

Abstract: We have searched for X-ray emission from a sample of five nearby (6-20 pc), strongly magnetic (10-200 MG), relatively cool (6000-14000 K), single white dwarfs, two of which may possess coronae. We detect one star (GR 290) at better than 99% confidence and give upper limits from Einstein Observatory IPG data for four others. The detected luminosities and limits are in the range 1.4-12.5 X 10 27 ergs s _1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Searches with Einstein and EXOSAT (Fontaine et al 1982;Arnaud et al 1992) and with ROSAT (Cavallo et al 1993;Musielak et al 1995) for coronal X-rays from cool white dwarfs yielded no firm detections. For searches with the ROSAT PSPC, Cavallo et al (1993) established X-ray upper limits for the white dwarfs G99-47 and G195-19;Musielak et al (1995) for GD 90, GD 356, and WD 2316+123.…”
Section: Previous X-ray Observationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Searches with Einstein and EXOSAT (Fontaine et al 1982;Arnaud et al 1992) and with ROSAT (Cavallo et al 1993;Musielak et al 1995) for coronal X-rays from cool white dwarfs yielded no firm detections. For searches with the ROSAT PSPC, Cavallo et al (1993) established X-ray upper limits for the white dwarfs G99-47 and G195-19;Musielak et al (1995) for GD 90, GD 356, and WD 2316+123.…”
Section: Previous X-ray Observationsmentioning
confidence: 95%
“…Several theorists (e.g., Zheleznyakov & Litvinchuk 1984;Serber 1990;Thomas, Markiel, & Van Horn 1995) have suggested that single, cool, magnetic white dwarfs might have coronae. Some observers (Fontaine, Montmerle, & Michaud 1982;Arnaud et al 1992;Cavallo, Arnaud, & Trimble 1993;Musielak, Porter, & Davis 1995;Musielak et al 2003) have previously searched for X radiation that might be emitted by hot gas above a white-dwarf photosphere. There were no persuasive detections, despite one false alarm -GR 290, in archival Einstein data (Arnaud et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromospheric activity (and an associated x-ray bright corona) is an obvious explanation, but no evidence for such a phenomenon has ever been detected from a magnetic white dwarf (e.g. Arnaud, Zheleznyakov andTrimble 1992, Cavallo, Arnaud andTrimble 1993). From ROSAT observations, Muielak, Porter and Davis (1995) give the upper limit on the x-ray luminosity of GD 356 at a few ×10 26 erg s −1 , the same order of magnitude as the luminosity of the solar corona.…”
Section: A Cool Spot Variability Modelmentioning
confidence: 99%
“…To quantify the uncertainties from the dark matter density distribution, we also show the sensitivities for the generalized Navarro-Frenk-White (gNFW) profile [549,550] and a density spike near the central black hole [551,552,553]. Additionally, it is possible that some white dwarfs might be surrounded by a hot envelope in the outer part of their atmosphere, a so-called "corona" [554,555], which was originally proposed to account for observations of X-ray emission from such stars [556]. However, these observations were later revisited and found to be either consistent with emissions from the photosphere or with a nondetection [557,556,558].…”
Section: Detection Sensitivitymentioning
confidence: 99%